Find the best solutions to your questions at Westonci.ca, the premier Q&A platform with a community of knowledgeable experts. Ask your questions and receive precise answers from experienced professionals across different disciplines. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.

−4(4x-6)= 3(-7x-1)

How do I solve this step by step when trying to solve for x?


Sagot :

The answer is [tex]x=-\frac{27}{5} [/tex]

Sulotion:

[tex]-4(4x-6)=3(-7x-1)[/tex]

[tex]-16x+24=3\left(-7x-1\right) [/tex]

[tex]-16x+24=-21x-3 [/tex]

[tex]-16x+24+21x=-3 [/tex]

[tex]5x+24=-3 [/tex]

[tex]5x=-3-24 [/tex]

[tex]5x=-27 [/tex]

[tex]x=\frac{-27}{5} [/tex]

[tex]x=-\frac{27}{5} [/tex]

Explanation:

#CarryOnLearning